High Gain, Wide Bandwidth and Optimal Swing op-amp in CMOS Technology - Emadi, Mohammad; Tavakoli, Mohammad Bagher (International Journal of Computer Sciences and Engineering, 2014)
Nowadays, operational amplifiers (op-amps) are widely used in numerous advanced electronic systems. Most of op-amps need a high gain, wide bandwidth, and an optimal swing. However, meeting these requirements all at the same time has been a challenging problem for analogue circuits designers. For different systems, many various structures have been used, and each has improved one of features of the amplifier in some way. In the present study, attempted was made to reach the best conditions for gain, bandwidth, and swing through appropriate parametric models. Of course, it is considered that the rest of circuit conditions do not undergo undesirable changes and get the best values [1].